Biology and Control of Horse Purslane and Common Purslane in Sugarcane - Dennis Calvin Odero; Ron Rice; Les Baucum (EDIS)
Horse purslane and common purslane are broadleaf weeds associated with sugarcane fields in muck (organic) and mineral soils of South Florida. Growers often confuse these two weed species with each other. However, these two species have distinct phylogenetic (evolutionary) and morphological differences. This 4-page fact sheet was written by Dennis Calvin Odero, Ron Rice, and Les Baucum, and published by the UF Department of Agronomy, January 2013.